Thirty years on. The implementation of Directive 93/13 on unfair terms, a joint and progressive task of legislators and judges - Jerez Delgado, Carmen; Verdún Pérez, Francisco (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
Thirty years after the publication of Directive 93/13 on unfair terms, the process of progressive implementation continues in Spain, both legally and jurisprudentially, in which the judges play an important role through the preliminary ruling question. This Directive is - like no other - a paradigm of the institutional game between the Member States and the European Union. The Spanish case is a case in point. A Directive that in principle has a material or substantive content has turned out to be a real Trojan horse in Spanish formal (procedural) law, altering its classic principles, to the astonishment of procedural doctrine.